Peranan Peer Group Communication Terhadap Literasi Safety Riding Komunitas Bikers Surabaya dalam aktifitas berkendara di Jalan Raya (Faculty of Communications Science, Dr. Soetomo University, 2018)
In line with economic growth in a positive direction followed by the increased consumption rate of motorized vehicles, moreover the facilities to obtain two-wheeled vehicles through credit are widely available. This phenomenon is also accompanied by the emergence of various types of two-wheeled communities and variants called the community of bikers. The number of bikers community contributes to traffic violations if community members do not understand driving safety safety riding. The National Police has carried out socialization to clubs or community bikers with various approaches, but the level of traffic violations on the highway is still high. The question is how is the biker community's safety riding literacy level? The role of peer group communication peer communication makes it possible to socialize and internalize safety riding among members of the community of bikers. To find out how the role of group communication in the safety riding behavior of the community of bikers researchers will conduct Kewancara and FGD on several community bikers including CB Surabaya Club, Honda club, Surabaya scooter club, which is the most existent community in Surabaya in carrying out activities on the highway, touring. Keywords: Literacy, riding safety